Exploring the effects of language on students' mathematics and science achievements in Southeast Asian countries using hierarchical liner modelling Modelling - Ismail, N.A. (2011)
The effect of language competence on students' achievement is an important issue and has implication for general educational and pedagogical policies. This has become a sensitive and controversial topic in many Asian countries. This paper reports on research based on a secondary analysis of the performance of pupils in three Southeast Asian countries in the Trends in International Mathematics and Science Study (TIMSS) 2007 in which students were examined via tests in mathematics and science. The aim of this study is to investigate the effect of language on students' performance in mathematics and science subjects, taking into account gender differences, socioeconomic status and attitude towards mathematics and science. Given the complexity of the data collected in TIMSS, multi-level modeling techniques are used to account for the clustering effects. School differences account for more than forty percent of the variations in student achievements in mathematics and science subjects for all Southeast Asian countries in this study with Malaysia having the highest percentages in both mathematics and science. While language has no significant effect on achievements among Indonesia students, it had a negative effect on mathematics achievement in Malaysia and a positive effect on science achievement in Singapore.